The Rise of Catalyst Informatics: Towards Catalyst Genomics. Issue 4 (15th January 2019) - Takahashi, Keisuke; Takahashi, Lauren; Miyazato, Itsuki; Fujima, Jun; Tanaka, Yuzuru; Uno, Takeaki; Satoh, Hiroko; Ohno, Koichi; Nishida, Mayumi; Hirai, Kenji; Ohyama, Junya; Nguyen, Thanh Nhat; et al.
Abstract: Catalysis research is on the verge of experiencing a paradigm shift regarding how catalysts are designed and characterized due to the rise of catalyst informatics. The details of catalyst informatics are reviewed where the following three key concepts are proposed: catalyst data, catalyst data to catalyst design via data science, and catalyst platform. Additionally, progress and opportunities within catalyst informatics are explored and introduced. If the field of catalyst informatics grows in the appropriate manner, the methods and approaches taken for catalyst design would be fundamentally altered, leading towards great advancement within catalysis research. Abstract : Data in, catalyst out : The emergence of catalyst informatics is introduced with an exploration of three key concepts: catalyst data, catalyst data to design via data science, and platform. The core idea of catalyst informatics is to design catalysts from catalyst data via data science. The current state of catalyst informatics is also reviewed in an effort to address issues and offer potential solutions to obstacles faced by the community.